2014
DOI: 10.2298/vsp1402167s
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health status and quality of life of homeless persons in Belgrade, Serbia

Abstract: Measures for prevention of homelessness should include: foundation of national registry of homeless persons, development of systemic multisectorial cooperation and special psychosocial intervention strategies. In homeless population, health care measures should be focused on prevention and treatment of mental health disorders and chronic somatic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…As it can be seen, findings revealed that one of the key problems afflicting homeless girls is the presence of anxiety and depression symptoms. This coincides with previous studies in other countries [49,61,62] that show that such groups suffer from these because of growing up among vulnerable conditions that constitute one of the predominant reasons for abandoning their homes and entering an organization. Also, it was observed that they tend to be unassertive because they exhibit greater difficulty in defending their rights and interests; they cannot express their ideas and feelings without being aggressive, and are hostile and unable to establish healthy relationships.…”
Section: Findings and Conclusionsupporting
confidence: 91%
“…As it can be seen, findings revealed that one of the key problems afflicting homeless girls is the presence of anxiety and depression symptoms. This coincides with previous studies in other countries [49,61,62] that show that such groups suffer from these because of growing up among vulnerable conditions that constitute one of the predominant reasons for abandoning their homes and entering an organization. Also, it was observed that they tend to be unassertive because they exhibit greater difficulty in defending their rights and interests; they cannot express their ideas and feelings without being aggressive, and are hostile and unable to establish healthy relationships.…”
Section: Findings and Conclusionsupporting
confidence: 91%
“…Of 2122 identified studies, 37 were identified as potentially-relevant (Table 1). These studies reported on 73 health screening or health assessment tools, across 11 domains: oral health [22–32]; health related quality of life, and health status [9, 3348]; nutrition [49–56]; psychological and cognitive function [9, 22, 34, 35, 41, 42, 44, 56–59]; substance use [28, 3336, 51, 57]; injury [29, 30, 36, 58]; chronic conditions [33, 44, 45, 60, 57]; demography and anthropometry [3440, 44, 49, 5155, 60]; functional decline and frailty [9, 37, 38, 54]; hearing and vision [9, 36, 61]; and pelvic floor health [9].…”
Section: Resultsmentioning
confidence: 99%
“…Relevant to homeless, but not specifically validated Retinal camera, ophthalmoscope, air puff tonometer [61]Adult populations internationally, relevant to homeless, but not specifically validatedDomain 9: Mental health, psychological and cognitive function Boston Naming Test (BNT) [59]Originally developed for individuals with aphasia or other language disturbance caused by stroke, Alzheimer’s disease, or other dementing disorder, now available for children. Relevant to homeless, but not specifically validated Centre for Epidemiological Studies Depression Scale [22]Children, adolescents and adults worldwide, relevant to homeless but not specifically validated Color Trails test [59]Children, adolescents and adults worldwide, relevant to homeless but not specifically validated Controlled Oral Word Association Test (FAS) [59]Adolescents and adults worldwide, relevant to homeless but not specifically validated Geriatric Depression Scale (GDS-12R) [56]Older adults, validated on healthy, medically ill and mild to moderately cognitively impaired older adults, relevant to homeless but not specifically validated Grooved Pegboard Test [59]Children, adolescents, adults, validated on many conditions, relevant to homeless but not specifically validated Mini Mental State Examination (MMSE) [10]Adults worldwide, relevant to homeless but not specifically validated Neuropsychological Assessment Questionnaire [59]Adults worldwide, relevant to homeless but not specifically validated Repeatable Battery for Assessment of Neuropsychological Status (RBANS) [58]Developed for adults with dementia, now validated on many conditions, and for children & adolescents, relevant to homeless but not specifically validated Rey-Osterrieth Complex Figure Design (Rey-O) [41]Children, adolescents, adults worldwide, tested for dementia, relevant to homeless but not specifically validated Ruff Figural Fluency Test (RFFT) [59]Adolescents and adults worldwide, relevant to homeless, but not specifically validated Stroop Color Word test [59]Children and adolescents The Beck Depression Inventory-II, BDI-II [35, 45][71]Adolescents and adults worldwide, validated for homeless men The Elderly Cognitive Assessment Questionnaire (ECAQ) [56]Adults worldwide, tested for older adults, relevant to ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nur in der Hälfte der eingeschlossenen Studien wurde der Begriff Wohnungslosigkeit hinreichend operationalisiert, sodass bereits vor diesem Hintergrund die Vergleichbarkeit eingeschränkt ist. Alternativ fungiert der Ort der Teilnehmer*innengewinnung in den Studien als Indikator für Wohnungslosigkeit, wodurch jedoch unterschiedliche Adressatenkreise der jeweiligen Hilfsund Unterbringungsangebote zusammen betrachtet werden [31][32][33][34]. Auch international wird "Wohnungslosigkeit" häufig nicht oder uneinheitlich definiert [35].…”
Section: Allgemeine Methodik Der Studien Im Vergleichunclassified